Ethnographic methods - O'Reilly, Karen (London : New York : Routledge, 2012)
This new edition of Karen O'Reilly's popular Ethnographic methods provides a comprehensive and accessible introduction to the technical, practical and philosophical issues that arise when employing traditional and innovative research methods in relation to human agents" ... "Following substantial revision and updating, the second edition includes new discussions of emerging practices such as reflexive ethnography and autoethnographic accounts, as well as an entire chapter dedicated to new directions in the field - including virtual, mobile, multi-sited and global ethnography."--Back cover
Includes bibliographical references and index.
Keywords: Ethnology -- Philosophy; Ethnology -- Comparative method